New genera, species and records of Doryctinae (Hymenoptera: Braconidae) from Brazil - Gadelha, Sian De Souza; Nunes, Juliano Fiorelini; Oliveira, Marcio Luiz De (Zootaxa, 2016)
Two new genera of Doryctinae (Hymenoptera: Braconidae) are described, Parsteres n. gen., Tuberatra n. gen., and are added to the identification key of Marsh (1997). Three new species are also described: P. pilosus n. sp., T. curvicauda n. sp., and Barbalhoa longicaudus n. sp. An identification key to the species of Barbalhoa Marsh, 2002 is presented, and nine species of the subfamily have their first record for Brazil.